Sexual behavior and awareness of Chinese university students in transition with implied risk of sexually transmitted diseases and HIV infection: A cross-sectional study - Ma Qiaoqin; Ono-Kihara Masako; Cong Liming; Xu Guozhang; Zamani Saman; Ravari Shahrzad; Kihara Masahiro (BMC, 2006)
Abstract Background The vulnerability of young people to HIV and the recent emergence of the HIV epidemic in China have made it urgent to assess and update the HIV/STD risk profile of Chinese young people. Methods A self-administered questionnaire survey with cross-sectional design was conducted among 22,493 undergraduate students in two universities in Ningbo, China. Bivariate trend analysis and multiple logistic regression analysis were used to compare sexual behaviors and awareness between grades. Results Of respondents, 17.6% of males and 8.6% of females reported being sexually active. Condom was reported never/rarely used by 35% of sexually active students in both genders in the previous year. Pregnancy and induced abortion had each been experienced by about 10% of sexually active female students and the female partners of male students, and about 1.5% of sexually active students of both genders reported being diagnosed with an STD. Multivariate analysis revealed that students in lower grades, compared to those in higher grades, were more likely to have become sexually active before university, to have become aware of sex before high school, and to have been exposed to pornographic media before the age of 17 years, and for sexually active respondents of both genders, to have engaged in sex without using a condom. Conclusion Sexual behaviors of Chinese university students are poorly protected and sexual behaviors and awareness may have been undergoing rapid change, becoming active earlier and more risky. If this trend continues, vulnerable sexual network will grow among them that allow more expansion of sexually transmitted diseases and HIV.